PENGARUH REMUNERASI, ROTASI DAN MUTASI TERHADAP KINERJA APARAT KEPOLISIAN RESOR BIMA - Rahmat Firdaus Putra; Amir Tengku Ramli; Made Yudhi Setiani (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
This study aims to describe the effect of remuneration, rotation and mutation on the performance of the Bima Resort Police. This research is a quantitative research that uses associative research, namely research that seeks the relationship between one variable and another variable. The population of this study were all Bima Resort Police officers who had been rotated and transferred in 2020, which were 54 people and were used as research samples. The research instrument used in collecting research data is a questionnaire containing questions related to research variables. Before being used to collect research data, the validity and reliability are tested first. Data analysis in analytical research is descriptive analysis and multiple linear regression analysis. The results of the descriptive analysis show that the remuneration variable for the members of the Bima Resort Police in 2021 is quite high, the rotation policy is classified as good in accordance with applicable regulations as well as the mutation policy which is classified as good and the results of the performance questionnaire for the members of the Bima Resort Police in 2021 are classified as high. The results of multiple linear regression analysis that: (1) remuneration has a significant effect on the performance of members of the Bima Resort Police; (2) The rotation policy has no significant effect on members of the Bima Resort Police; (3) The transfer policy has a significant effect on members of the Bima Resort Police; and (4) Remuneration, rotation and mutation have a significant simultaneous effect on members of the Bima Resort Police.